PERAN GURU SENI BUDAYA DALAM MENINGKATKAN MINAT BELAJAR SISWA DI ERA DIGITAL - Gusti Ayu Made Puspawati; Muh. Ibnan Syarif; Suharto (Widyadari, 2025)
This study investigates the role of arts and culture teachers in fostering student learning interest in the digital age. Arts education is crucial for shaping the character and creativity of the younger generation amidst rapid technological developments. As educators and mentors, arts teachers have a significant responsibility to connect advances in digital technology with traditional cultural values. This study conducted qualitative research involving observations and in-depth interviews with arts teachers in schools and arts education institutions. The results indicate that dance, visual arts, and music teachers not only teach arts skills but also encourage students to use digital technology for innovative artistic expression and to appreciate and preserve local culture. Furthermore, teachers are responsible for developing digital platforms that enable students to access arts resources from around the world. They are also responsible for creating learning environments that are more in line with technological advancements. This research demonstrates that enhancing digital skills for art teachers is crucial for enhancing the effectiveness of teaching and the relevance of traditional arts in the digital age. Furthermore, the results are expected to provide insights into creating arts education curricula that are more adaptive to changing times, particularly considering the challenges of increasing globalization.